A type-5 metabotropic glutamate receptor-perineuronal net axis shapes the function of cortical GABAergic interneurons in chronic pain - Giada Mascio; Ferdinando Nicoletti; Giuseppe Battaglia; Serena Notartomaso (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Parvalbumin-positive (PV+) interneurons (basket and chandelier cells) regulate the firing rate of pyramidal neurons in the cerebral cortex and play a key role in the generation of network oscillations in the cerebral cortex. A growing body of evidence suggest that cortical PV+ interneurons become overactive in chronic pain and contribute to nociceptive sensitization by inhibiting a top-down analgesic pathway. Here, we provide further support to this hypothesis showing that intracortical infusion of the GABA A receptor antagonist, bicuculline, caused analgesia in a mouse model of chronic inflammatory pain, although it reduced pain thresholds in healthy mice. We propose that mGlu5 metabotropic glutamate receptors and perineuronal nets (PNNs) shape the activity of PV+ interneurons in chronic pain, generating a form of maladaptive plasticity that enhances behavioural pain responses. mGlu5 receptors might be locally targeted by drugs activated by light delivered in cortical regions of the pain matrix, whereas the density of PNNs enwrapping PV+ interneurons might be reduced by local activation of PNN-degrading enzyme, such as type-9 matrix metalloproteinase. These strategies, which may require invasive treatments, might be beneficial in the management of severe pain which is refractory to conventional pharmacological and non-pharmacological interventions.